Differences of clinical features and outcomes between male and female elderly patients in gastric cancer - Hiroshi Arakawa; Shuhei Komatsu; Hajime Kamiya; Keiji Nishibeppu; Takuma Ohashi; Hirotaka Konishi; Atsushi Shiozaki; Takeshi Kubota; Hitoshi Fujiwara; Eigo Otsuji (Scientific Reports, 2023)
Abstract Although the average life span differs between males and females, little is known about differences in clinical features and short and long-term outcomes between elderly male and female gastric cancer patients. This study was designed to clarify these issues to identify the possibility for sex-based treatment strategies in elderly gastric cancer patients. This study included 295 consecutive elderly gastric cancer patients (75 years or older) who underwent curative gastrectomy between 1997 and 2016. We defined postoperative complications as Clavien–Dindo classification grade II or higher. Comorbidities were present in 67% of all patients. Males tended to have more comorbidities than females (P = 0.077). Male patients had significantly more upper gastric cancers (P = 0.001), a higher incidence of postoperative complications (P = 0.045), and poorer prognoses than females (P = 0.003). Multivariate analysis revealed that being male was an independent risk factor for postoperative complications (Odds ratio 2.5, P = 0.045) and a poor prognostic factor (Hazard ratio 1.81, P = 0.008). Patients who underwent limited surgery without postoperative complications tended to have a better prognosis than patients receiving standard surgery with postoperative complications (3-year overall survival: 78% vs. 55%, P = 0.156). Male was an independent risk factor for postoperative complications and an independent poor prognostic factor in elderly gastric cancer patients. To avoid postoperative complications, the limited surgery might be justified for high-risk elderly male patients.